Integrasi Nilai Pendidikan Ramah Lingkungan Dalam Kurikulum Pembelajaran Sejarah Indonesia: Kajian Literatur Terhadap Pendekatan Ecopedagogy - Ratu Rahmini; Miftahuddin Miftahuddin; Danu Eko Agustinova (LPPM Institut Pendidikan Nusantara Global, 2026)
The escalating global ecological crisis has urged a fundamental reorientation of education systems toward cultivating environmental awareness among younger generations. In the Indonesian context, history learning has remained predominantly focused on socio-political dimensions, leaving environmental education values largely unintegrated in a systematic and structured manner. This study aims to analyze the integration of environmentally friendly education values into the Indonesian history learning curriculum through the ecopedagogy approach, while simultaneously identifying conceptual models capable of supporting the realization of environmentally conscious history learning on a sustainable basis. A systematic literature review with a qualitative approach was employed, drawing on 12 indexed scientific journal articles selected through purposive sampling and analyzed using the Miles, Huberman, and Saldaña model. Three principal findings emerged: first, ecopedagogy possesses a robust theoretical foundation and can be integrated into several Basic Competencies of history subjects; second, local wisdom and green history serve as authentic mediums that reinforce ecopedagogy implementation through the representation of ecological values in textbooks and local traditions; third, implementation challenges including limited learning resources and insufficient teacher capacity require sustained policy support. Further empirical research is recommended to validate this conceptual framework through direct field-based studies.